Pertumbuhan dan Produksi Berbagai Varietas Bawang Merah (Allium AscalonicumL.) Asal Bijiyang Ditanam dengan Jarak Tanam Berbeda - Nurrahmi Yulfia; Gunawan Tabrani; Irfandri Irfandri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
This study aims to produce varieties of shallots (Allium ascalonicum L.) from seeds with better growth and production by adjusting the spacing. The research was conducted at the experimental garden of the Faculty of Agriculture, Riau University, Pekanbaru from May to October 2019, in a factorial completely randomized experimental design in three replications. The first factor is the variety (V), namely: v1 = Sanren, v2 = Lokananta, and v3 = Tuk Tuk. The second factor, the spacing plant (J) was: j1 = 10 cm x 10 cm, j2 = 10 cm x 15 cm, and j3 = 10 cm x 20 cm. The variables observed were plant height, number of leaves per tuber and per clump, leaf length, number of tubers per clump, tuber size, fresh weight and dry weight of tubers per plot. The research data were analyzed ofvariance and followed by orthogonal contrast test at 5% level. The results showed that the interaction between varieties and spacing plant was seen in: number of leaves per tuber and per clump. The number of tubers per hill, tuber diameter, fresh and dry weight of tubers per plot were affected by the variety. The number of tubers per hill and tuber diameter are also affected by spacing plant. Shallots of the Sanren variety increased, if planted at loose spacing, but the production was higher in the Tuk Tuk variety or when planted with more spacing. Keywords: True Shallot Seed, variety, plant spacing